2023
DOI: 10.1029/2022gl102579
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observational Evidence of Altered Mesosphere Lower Thermosphere Mean Circulation From a Major Sudden Stratospheric Warming

Abstract: Stratospheric sudden warmings (SSWs) are global-scale meteorological events driven by the dissipation of vertically propagating planetary waves originating in the troposphere (Butler et al., 2015;Matsuno, 1971). SSW events are characterized based on the changes that occur in the stratosphere, including a rapid increase in polar temperatures and deceleration of the zonal mean zonal winds. A SSW is classified as a major SSW if the zonal mean zonal winds at 60°N and 10 hPa reverse from eastward to westward (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(146 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, the amplitude of the migrating Sun-synchronous semidiurnal tide increases during SSWs in the low-and midlatitude lower and upper thermosphere (Goncharenko et al, 2010b;Liu et al, 2013;Oberheide, 2022). More recently, Gasperini et al (2023) analyzed ICON green line winds in the MLT, showing that the SW2 zonal wind amplitudes are amplified following the 2020/2021 major SSW, which we were able to confirm in our analysis (Section 3.2). These two changes can be related, because GWs are known to attenuate the semidiurnal tide in the thermosphere (Miyoshi and Yiğit, 2019).…”
Section: Mechanisms Of Thermal Changes and Connections To Winds In Th...supporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, the amplitude of the migrating Sun-synchronous semidiurnal tide increases during SSWs in the low-and midlatitude lower and upper thermosphere (Goncharenko et al, 2010b;Liu et al, 2013;Oberheide, 2022). More recently, Gasperini et al (2023) analyzed ICON green line winds in the MLT, showing that the SW2 zonal wind amplitudes are amplified following the 2020/2021 major SSW, which we were able to confirm in our analysis (Section 3.2). These two changes can be related, because GWs are known to attenuate the semidiurnal tide in the thermosphere (Miyoshi and Yiğit, 2019).…”
Section: Mechanisms Of Thermal Changes and Connections To Winds In Th...supporting
confidence: 80%
“…Also, high resolution first-principle GCMs show that the total GW energy and the associated drag decrease in the thermosphere above 110 km (Miyoshi et al, 2015), while observations show that nonmigrating tides amplify in the middle atmosphere (Pancheva et al, 2009). More recently, analysis of the ICON observations between 93 and 106 km indicated that the semidiurnal tidal and 3-day ultra-fast Kelvin wave activity contribute to the structure of the mean meridional circulation in the upper mesosphere and lower thermosphere (MLT) (Gasperini et al, 2023).…”
mentioning
confidence: 99%
“…The large gray arrows indicate the direction of the residual circulation. In the weak vortex case (Figures 5a and 5c), there is Equator to pole flow between 110 and 140 km, with descent at these altitudes over the pole, and ascent below (as indicated by the CO isoline from Figure 3a), consistent with Miyoshi et al (2015) and Gasperini et al (2023). In contrast, during the strong vortex event (Figures 5b and 5d), there is descent above 140 km over the pole and a pole-to-Equator flow between 110 and 140 km.…”
Section: Middle Atmosphere Conditions During the Weak And Strong Vort...mentioning
confidence: 59%
“…(2015) and Gasperini et al. (2023). In contrast, during the strong vortex event (Figures 5b and 5d), there is descent above 140 km over the pole and a pole‐to‐Equator flow between 110 and 140 km.…”
Section: Resultsmentioning
confidence: 95%